IMPLEMENTATION OF ARABIC LEARNING STRATEGIES THROUGH SHOBAHUL LUGHOH ACTIVITIES AT MTS AL HIDAYAH JATIGUNTING WONOREJO - Solihah, Nikmatus; Syaifullah, Syaifullah; Nurrokhmatulloh, Nurrokhmatulloh (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2025)
This study aims to describe the implementation of Arabic learning strategies through Shobahul Lughoh activities at MTs Al Hidayah Jatigunting Wonorejo, as well as to determine students' Arabic language skills as a result of the application of these strategies. The research method used is descriptive qualitative approach, with data collection techniques in the form of observation, interviews, and other supporting documentation. The results show that Shobahul Lughoh activities are carried out regularly every morning before learning begins, by involving all students in the practice of speaking Arabic through dialog, daily vocabulary, and simple expressions. This strategy is proven to be able to increase students' confidence, active participation, and speaking ability in Arabic, resulting in a conducive, communicative, and enthusiastic learning environment. This research also shows that language habituation through daily practice is effective in building students' communicative competence. Thus, the implementation of Shobahul Lughoh is one of the good and sustainable strategies in improving the quality of Arabic language learning at the madrasah tsanawiyah level.